Inokulasi Silang Patogen Collectotrichum gloeosporioides pada Tanaman Karet, Cabai Merah, Pepaya, dan Pisang - Harman Hamidson; Musliyadi Singarimbun; Abu Umayah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Hamidson H, Singarimbu M, Umayah A. 2021. Cross-inoculation of the pathogen collectotrichum gloeosporioides in rubber, red chilli, papaya, and banana plant. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 142-153. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The aim of this study was to determine the relationship and the level of virulence of C. gloeosporioides on rubber, chili, papaya, and banana plants. The study used a factorial randomized block design consisting of two factors. The factors included 4 types of inoculum sources and 4 types of host plant factors. The results of observations on the growth of C. gloeospporioides on PDA media showed that C. gloeosporioides as a source of banana inoculum had the highest growth rate of 16.8 mm/day followed by papaya 14.29 mm/day, rubber 9.04 mm/day and chili 6.69 mm. /day. The fastest incubation period from the chili inoculum source was in the CbiPp 4 hsi treatment, from the rubber inoculum source was in the KiPp 6 hsi treatment, from the papaya inoculum source was in the PpiK 4 hsi treatment, and from the banana inoculum source was in the PsiK and PsiPp 4 hsi treatment. Observation of the number of spots showed not insignificant effect on the inoculum source factor, significant effect on the plant factor the interaction between the two factors. Observation of spot diameter showed a very significant influence on the inoculum source factor, plants and their interactions. Cluster analysis using hierarchical method showed that Ppi and Psi were very close, slightly far from Cbi and very far from Ki. The relationship of each plant could be seen in chili and banana which were very close, a bit far from rubber plants and very far from papaya plants. The closeness of C. gloeosporioides to the host indicated by the correspondence analysis was seen between Ki and papaya, Cbi to chili, Psi to rubber and Ppi closer to papaya.